Phase Angle Is a Potential Novel Early Marker for Sarcopenia and Cognitive Impairment in the General Population - Kentaro Ikeue; Hisashi Kato; Masashi Tanaka; Hajime Yamakage; Sayaka Kato; Masayo Iwasa; Kan Oishi; Yuiko Yamamoto; Megumi Kanasaki; Izuru Masuda; Kojiro Ishii; Noriko Satoh‐Asahara (Journal of Cachexia, Sarcopenia and Muscle, 2025)
ABSTRACT Background Sarcopenia is associated with an increased risk for dementia. This study aimed to elucidate the relationship between sarcopenia‐related indices and cognitive decline in the general population. Methods This was a cross‐sectional study involving 263 participants (163 men with a median age of 60 years [interquartile range = 53–70] and 100 women with a median age of 58 years [interquartile range = 49–68]) who underwent a general health examination. Sarcopenia‐related indices included appendicular skeletal muscle mass (ASM)/height2, ASM/body mass index, handgrip strength (HGS), HGS/upper extremity skeletal muscle mass and phase angle (PhA). We examined the associations between these indices and cognitive function using the Japanese version of the Montreal Cognitive Assessment (MoCA‐J). Results Higher PhA, an indicator of muscle quality, was associated with a lower risk of mild cognitive impairment (MCI) in women (adjusted odds ratio = 0.28 [95% confidence interval, 0.10–0.78], p = 0.014), whereas the other sarcopenia‐related indices showed no significant association with MCI in both sexes. The PhA of women was positively associated with the MoCA‐J scores (β = 0.27, p = 0.005). Moreover, the PhA of women showed a positive correlation with cognitive subdomains, including memory (r = 0.22, p = 0.031), which is one of the earliest manifestations of cognitive impairment. The PhA in men was also positively correlated with memory (r = 0.24, p = 0.002). Conclusions PhA is a potentially novel index for detecting the risk of sarcopenia and cognitive decline in the general population.